Combining technologies and transformative approaches to gender in livestock and fish research - Kruijssen, Froukje (International Livestock Research Institute, 2016)
The best way to shift gender norms and dynamics is to link gender to other interventions. Addressing gender norms by themselves is difficult and is not easily accepted. The researchers introduced a new type of fishing net designed to catch small, nutritious fish known as mola. They tested whether the combination of gender-transformative approaches and technology would improve benefits and empowerment and have an effect on food security. In some communities they tried making gender norms a topic of discussion, bringing men, women, mothers-in-law, and community leaders together. In other communities, they introduced only the nets, without trying the gender-transformative approaches. They hope both to measure empowerment and to improve food security. Interview with Froukje Kruijssen (WorldFish) for the book "A different kettle of fish? Gender integration in livestock and fish research": http://hdl.handle.net/10568/76684